A manualised weight management programme for adults with mild–moderate intellectual disabilities affected by excess weight: A randomised controlled feasibility trial (Shape Up‐LD). Issue 1 (23rd July 2021) - Lally, Phillippa; Beeken, Rebecca J.; Wilson, Rose; Omar, Rumana; Hunter, Rachael; Fovargue, Sally; Anderson, Diana; King, Michael; Hassiotis, Angela; Croker, Helen
Abstract: Background: The aim was to pilot an adapted manualised weight management programme for persons with mild–moderate intellectual disabilities affected by overweight or obesity (' Shape Up‐LD '). Method: Adults with intellectual disabilities were enrolled in a 6‐month trial (3‐month active intervention and 3‐month follow‐up) and were individually randomised to Shape Up‐LD or a usual care control. Feasibility outcomes included recruitment, retention, initial effectiveness and cost. Results: Fifty people were enrolled. Follow‐up rates were 78% at 3 months and 74% at 6 months. At 3 and 6 months, controlling for baseline weight, no difference was observed between groups (3 months: β : −0.34, 95% confidence interval [CI]: −2.38, 1.69, 6 months: β : −0.55, 95%CI −4.34, 3.24). Conclusion: It may be possible to carry out a trial of Shape Up‐LD, although barriers to recruitment, carer engagement and questionnaire completion need to be addressed, alongside refinements to the intervention.